Characterization of Atomic Layer Deposited Cobalt Oxide. (19th June 2018) - Holden, Konner Eric Kurt; Jenkins, Melanie A.; Conley, John F.
Abstract : The electrical, optical, and structural properties of cobalt oxide films deposited via atomic layer deposition using Co(Cp)2 and O3 are investigated. At 250 °C, growth is 0.50 Å per cycle and smooth uniform films are deposited across a 5" wafer with atomic force microscopy showing a root mean square roughness of 0.4 nm. Spectroscopic ellipsometry indicates a refractive index of approximately 2.8 at 632.8 nm while grazing incidence X-ray diffraction of as-deposited films shows cubic Co3 O4, a p-type semiconducting phase. Semiconducting behavior is supported by current density versus electric field measurements.